Barriers to the effective treatment and prevention of malaria in Africa: A systematic review of qualitative studies - Mills Edward J; Mnyusiwalla Anisa; Maslove David M; McGowan Jessie; Attaran Amir; Wilson Kumanan (BMC, 2009)
Abstract Background In Africa, an estimated 300-500 million cases of malaria occur each year resulting in approximately 1 million deaths. More than 90% of these are in children under 5 years of age. To identify commonly held beliefs about malaria that might present barriers to its successful treatment and prevention, we conducted a systematic review of qualitative studies examining beliefs and practices concerning malaria in sub-Saharan African countries. Methods We searched Medline and Scopus (1966-2009) and identified 39 studies that employed qualitative methods (focus groups and interviews) to examine the knowledge, attitudes, and practices of people living in African countries where malaria is endemic. Data were extracted relating to study characteristics, and themes pertaining to barriers to malaria treatment and prevention. Results The majority of studies were conducted in rural areas, and focused mostly or entirely on children. Major barriers to prevention reported included a lack of understanding of the cause and transmission of malaria (29/39), the belief that malaria cannot be prevented (7/39), and the use of ineffective prevention measures (12/39). Thirty-seven of 39 articles identified barriers to malaria treatment, including concerns about the safety and efficacy of conventional medicines (15/39), logistical obstacles, and reliance on traditional remedies. Specific barriers to the treatment of childhood malaria identified included the belief that a child with convulsions could die if given an injection or taken to hospital (10/39). Conclusion These findings suggest that large-scale malaria prevention and treatment programs must account for the social and cultural contexts in which they are deployed. Further quantitative research should be undertaken to more precisely measure the impact of the themes uncovered by this exploratory analysis.